Art of Prevention: The importance of tackling the nail biting habit (2020)
Onychophagia, commonly referred to as nailbiting is a chronic condition that is repetitive and compulsive in nature, and generally seen in both children and young adults. Multiple factors play a role in the development of nailbiting, ranging from genetic components, to underlying psychiatric conditions. Complications of chronic, compulsive nail-biting range from obvious distortion of the nail bed unit, to ungual and oral infection. Dental hygiene is, typically, less well-maintained in patients with nail-biting disorders: teeth may become chipped or notched, and gums many become inflamed. Treatment of nailbiting involves a multidisciplinary team that provides social, psychiatric, dermatologic, and dental care. Treatment ranges from psychotherapy modalities, to medication trials of selective serotonin reuptake inhibitors and N-acetylcysteine. Proper nail hygiene remains a mainstay in the prevention of the complications of chronic nail-biting. Additional supportive measures include the support of self-motivational novels and television episodes that help children learn coping mechanisms.